Enzymatic synthesis of poly(ε-caprolactone-co-ε-thiocaprolactone). (February 2017) - Duchiron, Stéphane W.; Pollet, Eric; Givry, Sébastien; Avérous, Luc
Graphical abstract: Highlights: Successful synthesis of poly(ester- co -thioester) by eROP by different ways. Thermal properties tuning with enzymatically synthesized copolyesters. Trimerization step shown for the first time during eROP with immobilized lipase B. Controlled microstructures and architectures with multistep strategies by eROP. Abstract: This study presents the successful enzymatic ring opening copolymerization of ε-caprolactone (ε-CL) and ε-thiocaprolactone (ε-TCL) catalyzed by Novozyme 435, immobilized lipase B from Candida antarctica . Various monomers feed ratio (from 0 to 100% in TCL content) were tested using two polymerization strategies. The first one is a direct one-step strategy, starting with both monomers mixed in the feed, while the two-steps strategy consists in a first step of ε-CL homopolymerization followed by a second step with ε-TCL addition in the medium and its polymerization from the previously formed PCL chains. The obtained copolymers have been fully characterized by NMR, DSC, SEC and MALDI-ToF MS spectroscopy. Main results of the one-step strategy showed a decrease in the final copolymer molar mass with the increase in ε-TCL content as well as minimum values of crystallinity and melting temperature for the 50:50 feed composition. An in-depth analysis of the MALDI-TOF mass spectra of the copolymers showed interesting patterns that suggest a micro-structuration of polymers from the one step strategy resulting from an uncommon multistep chain growth mechanism of trimers addition. The two-steps strategy produced copolymers showing a more blocky structure, as confirmed by their two distinct melting temperatures.